MENINGKATKAN MINAT BELAJAR PESERTA DIDIK TERHADAP MATA PELAJARAN BAHASA INDONESIA DENGAN MENGGUNAKAN MEDIA QUIZIZZ: (Penelitian Tindakan Kelas Pada Materi Ekspresi Diri melalui Hobi Peserta Didik Kelas V SDN 1 Nusawangi) - Shakila Rostika Dewi; Deni Chandra; Febri Fajar Pratama (STKIP Subang, 2025)
Students' interest in learning Indonesian in the fifth grade of SDN 1 Nusawangi was relatively low, as seen from their lack of enthusiasm during lessons, such as not paying attention to the teacher, talking to peers, and reluctance to ask questions. This study aimed to increase students' learning interest by using the Quizizz learning media in the material on self-expression through hobbies. The study employed Classroom Action Research (CAR) following the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection. The subjects were 30 fifth-grade students of SDN 1 Nusawangi. Data were collected through observation, documentation, and learning evaluation tests. The results indicated that the use of Quizizz successfully enhanced students' learning interest, shown through improvements in four indicators: enjoyment, curiosity, attention, and engagement. The percentage of learning mastery increased from 60% in the pre-cycle to 76.6% in cycle I and reached 90% in cycle II. It is concluded that Quizizz is an effective, fun, and interactive learning tool that can significantly improve students' interest in learning Indonesian.